If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 + 2x + -22 = 3x + -18 Reorder the terms: 10 + -22 + 2x + 2x = 3x + -18 Combine like terms: 10 + -22 = -12 -12 + 2x + 2x = 3x + -18 Combine like terms: 2x + 2x = 4x -12 + 4x = 3x + -18 Reorder the terms: -12 + 4x = -18 + 3x Solving -12 + 4x = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 4x + -3x = -18 + 3x + -3x Combine like terms: 4x + -3x = 1x -12 + 1x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 1x = -18 + 0 -12 + 1x = -18 Add '12' to each side of the equation. -12 + 12 + 1x = -18 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = -18 + 12 1x = -18 + 12 Combine like terms: -18 + 12 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| .4(x+2.4)=2.96 | | (4x+9)+(2x-12)= | | 27x-36-14x+63=300 | | 4.5(x-9)=-25 | | 19-7m=14-6m | | 3/16-1/4 | | 5t^2+t=42 | | 2x-4(3x+1)-5= | | 3x-10+x+15=25 | | 11x-14=3x-14 | | x-1/x^3+2x | | N+17=14+3 | | -6+-12+-10+25= | | (x-3)squared=25 | | 3x^2+9=x^2+27 | | (x-3)/2=25 | | 6x^3-x^2-2x=0 | | 5x/2+12=-8 | | 5g+2g=7g | | 6-7g=-8 | | 6x+10y=50 | | x^3-9x^2+22x-15=0 | | 3n^2-5=0 | | 34-3w=25 | | 8x(8x-7)+-8x(9x-8)= | | 4-1/2 | | -50+87x=-75x^2-8x | | 8m^2+5m+4=7+3m | | 1/2*1/4 | | u+12u+17=0 | | x*x^3*x^3= | | (b^2+3b-9)/(b+5) |